1998
DOI: 10.1063/1.121527
|View full text |Cite
|
Sign up to set email alerts
|

Surface photovoltage spectroscopy of n-n+ and p-n+ AlGaAs/GaAs heterojunctions

Abstract: A comparative study of n-n+ and p-n+ semiconductor heterojunctions has been done using the surface photovoltage spectroscopy (SPS) in the chopped light geometry. Heterojunctions n-Al0.4Ga0.6As/n+ GaAs and p-Al0.37Ga0.67As/n+ GaAs and substrate n+ doped GaAs have been studied in the wavelength range 600–1000 nm. A sharp decrease in SPS at the band-gap energies of AlGaAs and GaAs with a broad peak in the subband-gap region of GaAs has been observed. The magnitude of surface photovoltage (SPV), for a constant pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…However, the interpretation of the slope sign of these 'knees' is considerably more complicated because in heterointerfaces the direction of the band-bending is not determined solely by depletion or accumulation and because some overlayers cause a reduction in SPV signal via simple absorption. 2 Some notable, recent applications of SPS to heterostructures include studies of defects, bandgaps and band-bendings at Si/porous-Si bilayers, 39,59 InP-based heterostructures, 10,60 GaAs/AlGaAs heterostructures, 61,62 the organic/inorganic p-dithioketopyrrolopyrrole (DTPP)/ SnO 2 :F heterojunction, 35 υ-doped GaAs layers, 63 GaN/ InGaN heterostructures 40 and even BaTiO 3 /Si heterostructures. 64 In a similar fashion, SPS allows for the characterization of quantum wells and other low-dimensional heterostructures.…”
Section: Characterization Of Multilayer Structuresmentioning
confidence: 99%
“…However, the interpretation of the slope sign of these 'knees' is considerably more complicated because in heterointerfaces the direction of the band-bending is not determined solely by depletion or accumulation and because some overlayers cause a reduction in SPV signal via simple absorption. 2 Some notable, recent applications of SPS to heterostructures include studies of defects, bandgaps and band-bendings at Si/porous-Si bilayers, 39,59 InP-based heterostructures, 10,60 GaAs/AlGaAs heterostructures, 61,62 the organic/inorganic p-dithioketopyrrolopyrrole (DTPP)/ SnO 2 :F heterojunction, 35 υ-doped GaAs layers, 63 GaN/ InGaN heterostructures 40 and even BaTiO 3 /Si heterostructures. 64 In a similar fashion, SPS allows for the characterization of quantum wells and other low-dimensional heterostructures.…”
Section: Characterization Of Multilayer Structuresmentioning
confidence: 99%
“…The distribution of relaxation rate appears due to magnetic glassiness, which has also been witnessed in the bifurcation of ZFC-FC plot. In order to strengthen the aforementioned indications of the growing FM interactions in addition to AFM/PM, we have fitted our M-H results to the following expression consisting of FM and AFM/PM parts [47], emu/g•Oe to 2.817×10 -5 emu/g•Oe, as x increases from 0.005 to 0.02, respectively. One aspect of this increase in the present scenario may be considered as the decrease in frustration parameter f =│θCW│/TN.…”
Section: B DC Magnetizationmentioning
confidence: 89%
“…The change in surface potential due to the light illumination is recorded by an indium‐tin‐oxide coated transparent‐conducting‐glass (TCG) plate that is kept in a soft‐contact mode on the sample (metal–insulator–semiconductor geometry); see Figure 1b. [ 27,28 ] The SPV signal is measured by a mechanical chopper and lock‐in amplifier configuration. Measurements are performed at 67 Hz chopping frequency unless otherwise specified.…”
Section: Methodsmentioning
confidence: 99%
“…With this in mind, surface photovoltage (SPV) spectroscopy, a non‐invasive technique, has been emerged as an excellent alternative tool to probe the abovementioned processes in semiconductor bulk and heterostructures. [ 25–31 ] An ample amount of research has been performed to realize the temperature, chopping frequency, and excitation power‐dependent SPV spectra. [ 32–34 ] Also, it has been shown that the SPV amplitude and phase spectra can be used to identify the energy eigenstates of quantum/superlattice structures, and their spectral features can be explained by non‐linear processes using a vector model.…”
Section: Introductionmentioning
confidence: 99%